Specificity regime of sediment runoff of the Ile River and estimating volume of suspended sediment sink in the Kapshagai Reservoir. (Journal of Geography and Environmental Management, 2016)
The scientific article is devoted to study of sediment runoff in the lower stream of the Ile River. Analyse the impact Kapshagai Reservoir on the regime and characteristics of sediment flow of the Ile River down stream was done. Together with the calculation of the characteristics of sediment runoff an assessment of suspended sediment deposited in the reservoir was done also.